The Influence of Breastfeeding On Nutritional Status, and the Frequency of Children Experience Tropical Diseases during the Covid 19 Pandemic in Samarinda - Ida Ayu Kade Sri Widiastuti; Ruminem Ruminem; Rita Puspa Sari; Bahtiar Bahtiar; Made Ermayani (Jurnal Kesehatan Pasak Bumi Kalimantan, 2023)
Warm temperatures, humidity, and high rainfall are factors in the high incidence of infectious diseases in the tropics. This condition is certainly risky for children's health. COVID-19 pandemic also adds to the risk of endangering the health of children in the golden period. In the golden period, infants and toddlers need adequate nutritional intake. Many factors hinder the provision of nutrition (ASI), one of which is the COVID 19 pandemic. Inadequate nutritional intake can lead to suboptimal growth and development of children, decreased immunity. The purpose of this study was to determine the effect of breastfeeding on nutritional status, and the frequency of children experiencing tropical diseases during the COVID 19 pandemic. Methods: Quantitative study with a categorical analytic research design. with a cross-sectional analytic approach. The sampling technique used a purposive sampling technique and the data collection tool was a questionnaire to measure the frequency of illness. Nutritional status measurement used anthropometric assessment. Conclusion: there is a significant relationship between breastfeeding and nutritional status and the frequency of illness in children. Recomedations:Therefore it is Important to campaign more intensively on the importance of breastfeeding for children's nutritional adequacy.